ANALISIS KINERJA KOPERASI SYARIAH BMT TRANS MEKAR SARI MANDIRI DI WILAYAH PERTANIAN KECAMATAN TANJUNG LAGO PADA MASA PENDEMI COVID-19 - Nirmala Jayanti; Rizky Tirta Adhiguna; Yuwinti Nearti (Jurnal Prodi Agribisnis, 2022)
Non-bank financial institutions that can be used as a solution in dealing with the problem of limitedcapital owned by business actors in the agricultural sector and which are quite familiar in the life offarmers are cooperatives. One of the efforts to increase the development of cooperatives in a positivedirection is to improve the performance of cooperatives in the aspects of capital, productive assetquality, management, efficiency, liquidity, independence and growth, cooperative identity and shariaprinciples. The performance assessment of sharia cooperatives can be carried out through theapplication of the Regulation of the Ministry of Cooperatives and Small and Medium Enterprises of theRepublic of Indonesia Number: 07/Per/Dep/2016 concerning the Implementation of Sharia Savingsand Loans and Financing Business Activities by Cooperatives. Each aspect is given a weight andthen a score is obtained to determine the predicate of cooperatives ranging from very unhealthy tohealthy. This research was conducted at the Trans Mekar Sari Mandiri BMT Cooperative in theagricultural area of the Tanjung Lago sub-district which was also affected by the COVID-19pandemic, namely a decrease in remaining operating results and an increase in member non- performing loans. The research was conducted using survey methods and direct field interviews withrespondents. Sampling was carried out using a gradual sampling method (Multiple Sampling) with asample of 33 respondents. The data collected is in the form of RAT data for the 2021 financial year. The results of the study state that the performance assessment of the Trans Mekar Sari Mandiri BMTCooperative during the COVID-19 pandemic showed a fairly healthy predicate but there were stillmany shortcomings in aspects of the quality of productive assets and aspects of liquidity.